Actinic cheilitis in rural workers: a literature review (Research, Society and Development, 2020)
It is known that cancer is one of the diseases that most affects the Brazilian population, it is extremely necessary to pay more attention to the early diagnosis of pre-malignant lesions such as leukoplakia, erythroplasia and actinic queillitis. All of them have as causes besides intrinsic factors to the individual, the involvement of environmental factors. Among these, solar radiation is one of the most important, especially in the development of actinic queillitis, which is caused by excessive exposure to solar radiation without protective factors, so it is important to conduct studies on the lesions in specific populations such as rural workers. The objective of the present study was to conduct a literature review on actinic queillitis in rural workers, addressing clinical and histological characteristics, prevalence data and use of protective factors. The methodology was based on a data collection through articles published between 2001 and 2020 in the PUBMED (United States National Library of Medicine), SCIELO (Scientific Electronic Library Online), Google Academic and Virtual Health Library (VHL) databases. Data from the literature show the greater predisposition of rural workers to the development of queilitis, requiring knowledge of health professionals about the clinical characteristics to perform early diagnosis and provide guidance and instruction to carriers.